Brain Sparing in Fetal Mice: BOLD MRI and Doppler Ultrasound Show Blood Redistribution During Hypoxia. Issue 6 (June 2014) - Cahill, Lindsay S; Zhou, Yu-Qing; Seed, Mike; Macgowan, Christopher K; Sled, John G
Mice reproduce many features of human pregnancy and have been widely used to model disorders of pregnancy. However, it has not been known whether fetal mice reproduce the physiologic response to hypoxia known as brain sparing, where blood flow is redistributed to preserve oxygenation of the brain at the expense of other fetal organs. In the present study, blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI) and Doppler ultrasound were used to determine the effect of acute hypoxia on the fetal blood flow in healthy, pregnant mice. As the maternal inspired gas mixture was varied between 100% and 8% oxygen on the timescale of minutes, the BOLD signal intensity decreased by 44 ± 18% in the fetal liver and by 12 ± 7% in the fetal brain. Using Doppler ultrasound measurements, mean cerebral blood velocity was observed to rise by 15 ± 8% under hypoxic conditions relative to hyperoxia. These findings are consistent with active regulation of cerebral oxygenation and clearly show brain sparing in fetal mice.